2019
DOI: 10.1186/s13244-019-0793-8
|View full text |Cite|
|
Sign up to set email alerts
|

Advanced imaging in adult diffusely infiltrating low-grade gliomas

Abstract: The adult diffusely infiltrating low-grade gliomas (LGGs) are typically IDH mutant and slow-growing gliomas having moderately increased cellularity generally without mitosis, necrosis, and microvascular proliferation. Supra-total resection of LGG significantly increases the overall survival by delaying malignant transformation compared with a simple debulking so accurate MR diagnosis is crucial for treatment planning. Data from meta-analysis support the addition of diffusion and perfusion-weighted MR imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…These results are consistent with the recent literature [10,20]. Indeed, after the 2016 WHO brain tumor classification update, some studies investigated the role of MRI in the prediction of the IDH mutational status in gliomas [15][16][17][18][19][20][21]. However, most of them evaluated the imaging characteristics of IDH molecular subgroups of mixed patient's samples, from grade II to grade IV gliomas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with the recent literature [10,20]. Indeed, after the 2016 WHO brain tumor classification update, some studies investigated the role of MRI in the prediction of the IDH mutational status in gliomas [15][16][17][18][19][20][21]. However, most of them evaluated the imaging characteristics of IDH molecular subgroups of mixed patient's samples, from grade II to grade IV gliomas.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, inverse significant correlations between ADC, cell count and ki67 have been reported [12,13]. Recently, some studies have shown that ADC maps may easily discriminate the IDH mutations status, but most of them did not consider a homogeneous group of gliomas in terms of grading and histology [14][15][16][17][18]. Indeed, ADC can be influenced by histology and grading [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted MR imaging together with ADC maps reflect hindered and restricted diffusion pools within a voxel on diffusion-weighted MR images. This is always in the routine diagnostic protocol, but diffusion kurtosis imaging is usually reserved for research purposes [ 28 ]. Within a specific ROI, areas of necrosis and peritumoral edema can increase ADC values, which increase cellular density architecture due to the reduced ADC values [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ADC threshold value of 1185 × 10 −6 mm 2 /s has a sensitivity of 97.6% and specificity of 53.1% in the discrimination of high-grade (grades III and IV) and low-grade (grade II) gliomas. Regarding tumor physical processes, MRS can be used to study tumor biomarkers such as IDH mutations, morphological image processing for quantitative analysis, and metabolism in noninvasive investigations of the link between the molecular basis of GBM and imaging attributes [ 27 , 28 ]. Most high-grade tumors have greater choline concentrations in astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, low grade tumors appear hyperintense on a FLAIR sequence with or without clear margins. On the pre-contrast T1-weighted sequences, the lesions tend to be hypointense and typically do not enhance following administration of gadolinium based agents (Forst et al, 2014;Bulakbaşı and Paksoy, 2019).…”
Section: Introductionmentioning
confidence: 99%